Acceptance of Skipjack Tuna Fish Nuggets with Moringa Leaves to Prevent Stunting in Toddlers - Sari, Rasidah Wahyuni; Nurlinda; Nurul Mutmainnah (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: The problem of stunting in toddlers is a priority for handling because it threatens human quality. Providing nutritious local food rich in animal protein is the key to handling toddler nutrition because it provides essential amino acids. One of the local foods that is rich in protein and easy to obtain in South Sulawesi is Skipjack Tuna (Katsuwonus pelamis) which contains complete protein and is rich in omega-3 fatty acids. Another local food is Moringa leaves (Moringa oleifera) which contain protein, vitamin A, and iron. This study aims to formulate and test the acceptability of skipjack tuna nuggets with the addition of moringa leaves.. Method: This research was conducted in August-September 2024. The formulation process of Skipjack Tuna and Moringa Leaf Nuggets was carried out at the Nutrition Laboratory of the Muhammadiyah University of Parepare, followed by testing the nutritional content at the Makassar Health Center and then organoleptic testing was carried out in Parepare City. The research sample consisted of 15 parents who had toddlers aged 24 months to 59 months by purposive sampling. Result: This research was conducted in August-September 2024. The formulation process of Skipjack Tuna and Moringa Leaf Nuggets was carried out at the Nutrition Laboratory of Muhammadiyah University of Parepare, nutritional content testing at BBLK Makassar and then organoleptic testing on a research sample of 15 parents who have toddlers aged 24 months to 59 months using purposive sampling. Conclusion: Formulation F1 has the highest protein and carbohydrate content, while Formulation F2 has the highest fat content. The results of the organoleptic test showed that Formulation F2 was considered the most preferred by respondents, with the highest values for color, aroma, and taste, while Formulation F1 had the highest value for texture.